41.6k views
0 votes
4. The difference log2 (3) - log2 (12) is equal to

User Hlynbech
by
5.1k points

2 Answers

5 votes

Answer:

-2

Explanation:


log_2(3)-log_2(12)

~Simplify using log properties


log_2((3)/(12))


log_2((1)/(4))

~Apply log rules


-log_2(4)

~Rewrite


-log_2(2^2)

~Apply log rules


-2log_2(2)

~Apply log rules

-2 * 1

~Simplify

-2

Best of Luck!

User Aric Lasry
by
5.2k points
1 vote

Answer:

Explanation:

-2

Apply this particular rule of logs:

log a - log b = log a/b

Therefore, log2 (3) - log2 (12) = log2 (3/12) = log2 (1/4)

This last result simplifies to log2 1 - log2 4 = 0 - 2 = -2

User Jagough
by
4.6k points